2001
DOI: 10.1016/s0020-7292(01)00423-4
|View full text |Cite
|
Sign up to set email alerts
|

Computerized analysis of fetal heart rate parameters by gestational age

Abstract: The results showed that overall, the differences in the FHR parameters between gestational groups were statistically significant, and the gestational age of the fetus should be considered when interpreting FHR patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 15 publications
6
30
0
6
Order By: Relevance
“…13 More recently, new studies have confirmed the increased frequency of accelerations after 32 weeks, as assessed by computerized cardiotocography, 14,15 confirming previous results and supporting the importance of these values once again to assess the proper development of the fetus.…”
Section: Discussionsupporting
confidence: 69%
“…13 More recently, new studies have confirmed the increased frequency of accelerations after 32 weeks, as assessed by computerized cardiotocography, 14,15 confirming previous results and supporting the importance of these values once again to assess the proper development of the fetus.…”
Section: Discussionsupporting
confidence: 69%
“…FHR parameters were monitored using an external electronic FHR monitor using our computerized Hanyang Fetal Monitoring System (HYFM-II) [2,14] . All the subjects were in a semirecumbent position for a minimum of 10 min before data collection which occurred from 2 to 6 p.m. FHR time series were recorded for more than 40 min using the HYFM; external fetal movements (FMs) and breathing were included.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%
“…FMs were recorded simultaneously. All data were sent to a given unit, and the interval was calculated at an average of 100 ms, as previously described by Park et al [2] . After signal loss was excluded, all remaining data were measured to obtain an average value of the total within the observational window of 20 min.…”
Section: Fhr Parameters and Reactive Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the major limitations are related to the few attempts to evaluate clinical implication of cCTG parameters as the absence of their analysis in relation with neonatal outcome. Most of the studies focussed on the predictive value of cCTG parameters considered only their relation with the Apgar score, not including other important parameters such as umbilical cord pH at birth (Bernardes et al 1997;Park et al 2001).…”
Section: Introductionmentioning
confidence: 99%